Export Performance Analysis on Indonesian Yellowfin Thunas (HS 030342) in the United States Market - Datau, Noufaldo Rahmatullah; Hendrati, Ignatia Martha (Gorontalo State University, 2024)
Tuna is a major fish commodity that has high economic value that dominates the export market of Indonesian fishery industry products. This study was carried out to analyze competitiveness, comparative advantage, trading patterns and trends of Indonesian tuna exports in the United States market from 2013-2022 using the Revealed Comparative Advantage (RCA), Revealed Symmetric Comparative Advantage (RSCA), and Constant Market Share (CMS). The results showed that Indonesia's RCA value is above one (>1) during the 2013-2022 period, meaning that Indonesian tuna has competitiveness, the RSCA value is also above one (>0), meaning that Indonesian tuna has a comparative advantage. According to the CMS analysis, Indonesia's growth of standard exports to the United States is still lower than the growth of world standard exports to the United States so that Indonesia's export performance is still relatively low. The distribution effect of the Indonesian tuna market shows a positive value which means that Indonesia has succeeded in showing good product distribution performance to the market. The effect of commodity composition and the effect of competitiveness of Indonesian tuna shows a negative value so that Indonesia is considered to have not met the market and is less competitive.